The Effect of Range of Motion (ROM) Exercises on the Occurrence of Neuropathy and Angiopathy - Wibowo, Harry Permana; Basri, Basri (Jurnal Keperawatan Priority, 2025)
Ankle ROM training involves two movements: dorsiflexion and plantarflexion, which enhances calf muscle strength and pumping, facilitating venous return and reducing oxygen and nutrient diffusion, thus promoting overall health. This study provides active lower ROM intervention to diabetes mellitus patients twice a day for 6 consecutive days simultaneously. This type of research uses quasi-experimental research using two groups pretest-posttest, namely an experimental design where there are control and intervention groups. The samples in this study were 35, of which 17 samples were for the intervention group and 18 samples were for the control group. The research found that ankle ROM exercises significantly improved the DNE score and ABI value in both the intervention and control groups, with a statistical test result of p = 0.000 in the DNE score. It can be believed that there is a significant difference between the DNE scores of the intervention group, and the control group after doing ankle ROM exercises (p = 0.000), then H0 was rejected or there was an effect of ROM exercises on reducing the risk of neuropathy. Meanwhile, the ABI value showed a statistical test result of p = 0.002 and it can be believed that there is a significant difference between the ABI values of the intervention group and the control group after ankle ROM exercises (p = 0.002), so H0 is rejected or there is an effect of ROM exercises on reducing the risk of Angiopathy.